2011
DOI: 10.1007/s12177-011-9074-6
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β and mitochondria damage, and the development of diabetic retinopathy

Abstract: Mitochondrial dysfunction is considered to play an important role in the development of diabetic retinopathy. Recent evidence has also shown many similarities between diabetic retinopathy and a low grade chronic inflammatory disease. The aim of this study is to understand the interrelationship between proinflammtory mediator, IL-1β and mitochondrial dysfunction in the accelerated loss of capillary cells in the retina. Using IL-1β receptor gene knockout (IL-1R1 − / − ) diabetic mice, we have investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…13 Immune function and inflammatory activity has been shown to be associated with circadian rhythm, with the peak of inflammatory activity occurring during the beginning of the sleep cycle. 49 Numerous studies demonstrated critical involvement of IL-1b in the pathogenesis of DR. 50,51 Indeed, IL-1b concentration is increased in diabetic retina. 34 Furthermore, blocking IL-1b production or signaling was shown to prevent vascular damage in the DR animal model.…”
Section: Discussionmentioning
confidence: 99%
“…13 Immune function and inflammatory activity has been shown to be associated with circadian rhythm, with the peak of inflammatory activity occurring during the beginning of the sleep cycle. 49 Numerous studies demonstrated critical involvement of IL-1b in the pathogenesis of DR. 50,51 Indeed, IL-1b concentration is increased in diabetic retina. 34 Furthermore, blocking IL-1b production or signaling was shown to prevent vascular damage in the DR animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of proapoptotic Bax to antiapoptotic Bcl-2 in the retina reflects the level of retinal cell apoptosis in diabetic rats [ 31 ]. A previous study found that IL-1 β induced retinal mitochondrial dysfunction, mitochondrial DNA damage, and cell apoptosis [ 32 ]. Bax is a marker of mitochondrial stress associated with vascular diabetes complications [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β is a key inflammatory cytokine regulated by the inflammasome, and increased levels of IL‐1β are present in DR (Kowluru et al, ; Liu et al, ) and AMD (Lavalette et al, ; Tarallo et al, ). Amelioration of IL‐1β activation prevents mitochondrial dysfunction and DNA damage (Kowluru et al, ). Furthermore, glucose‐induced apoptosis of retinal endothelial cells is prevented by neutralization of IL‐1β through incubating the cells with an IL‐1β antibody or IL‐1β receptor antagonist (Kowluru & Odenbach, ).…”
Section: Targeting Inflammasome Activation In Retinal Degenerative DImentioning
confidence: 99%